Features of molecular plasma SNF after heating and ionization - Yuferov, V.B.; Katrechko, V.V.; Mufel, E.V.; Svichkar, A.S.; Ilichova, V.O.; Khizhnyak, S.N.; Shariy, S.V. (Вопросы атомной науки и техники, 2014)
The analysis of the multicomponent composition of spent nuclear fuel (SNF) is presented. The possibility of SNF separation from the fission products (FP) upon heating, evaporation and ionization (at difference of the ionization potentials and dissociation energies) is considered. Further SNF posttreatment from FP is carried out by plasma methods. It is shown that for simulation of the SNF reprocessing in this stage the most appropriate medium is oxide plasma of nonradioactive ²³⁸U, Zr, Nb, Mo and lanthanides.